Development of Closed Organa Pipe Props as Learning Media to Determine the Speed of Sound Propagation in Air Assisted by Physics Toolbox Sensor Suite - Maghfiroh, Dhela Rochmatul; Sucahyo, Imam (Mitra Edukasi dan Publikasi, 2023)
Teaching aids can help students to gain an understanding of the concepts they learn. Based on the facts obtained at SMAN 1 Waru through teacher interviews and observations of the physics laboratory, the sound wave material of the sound source sub-chapter on organ pipes has never been practiced. The school needs more props to facilitate organ pipe practicum activities. This development's main objective is to create feasible closed organ pipe props in terms of accuracy and precision of sound propagation speed. The analysis stage is the initial stage in the ADDIE model development research. The ADDIE model development research carried out only until the Development stage, because the purpose of this research is only limited to developing and conducting trials in terms of accuracy and precision of the data obtained to produce a closed organa pipe props as a valid learning media to be implemented based on the validator's assessment. The speed of propagation of sound in air is obtained by multiplying the frequency value by the wavelength. The average value of the wavelength produced is (344.22 ± 0.034) m/s. The value of the sound propagation speed in the air produced using the developed closed organa pipe is not exactly the same as the theory but the value is almost close. The difference between the speed of propagation of sound in the air by experiment and theory is 1.22, so with a precision of 99.99% and the percentage of accuracy error is 99.65%, it is classified as a fairly high level of accuracy. Therefore, it can be concluded that the developed closed organa pipe props can be used as learning media to determine the value of sound propagation velocity.